Pediatric MR Imaging with Automated Spine Survey Iterative Scan Technique (ASSIST) - Weiss, K.L.; Sun, D.; Weiss, J.L. (American Journal of Neuroradiology, 2009)
SUMMARY: MR imaging automated spine survey iterative scan technique (ASSIST) provides an automated subminute, submillimeter, in-plane resolution survey of the entire spine in 2 contiguous sagittal fast gradient-echo breath-hold series with computer labeling of vertebrae and disks. The technique was prospectively tested in 13 school-aged children for a wide range of clinical indications. In all cases, imaging was successful without requiring repeated sequencing. In all but 1 patient manifesting prominent scoliosis, automated labeling was concordant with neuroradiologist assignments.